Challenges in the classification of fibrotic ILD: Patient case 1 - Manali, Effrosyni D. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
Patient presentation and clinical historyThe patient is a 43-year-old male non-smoker who works as a farmer and cheese-maker. He complained of a dry cough for 6–12 months without fever or other clinical signs. His medical history was unremarkable with no use of drugs or alcohol and no signs of Raynaud’s syndrome. In his family history he had two first-degree relatives with pulmonary fibrosis, one of whom also had rheumatoid arthritis.[...]